2011
DOI: 10.1039/b820255a
|View full text |Cite
|
Sign up to set email alerts
|

DNA as supramolecular scaffold for functional molecules: progress in DNA nanotechnology

Abstract: Oligonucleotides have recently gained increased attraction as a supramolecular scaffold for the design and synthesis of functional molecules on the nanometre scale. This tutorial review focuses on the recent progress in this highly active field of research with an emphasis on covalent modifications of DNA; non-covalent interactions of DNA with molecules such as groove binders or intercalators are not part of this review. Both terminal and internal modifications are covered, and the various points of attachment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
160
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(161 citation statements)
references
References 76 publications
0
160
0
1
Order By: Relevance
“…Thus, the mutual recognition of DNA conjugates can be used for the precise positioning of functional groups. For example, chromophores, [1] metals, [2] catalytic units, [3] nanoparticles, [4] fluorophores [5] and even proteins [6] have been arranged at well-defined distances by means of DNA hybridization. Until recently, the main interest was focused on issues within materials science as well as on the immobilization of biomolecules.…”
mentioning
confidence: 99%
“…Thus, the mutual recognition of DNA conjugates can be used for the precise positioning of functional groups. For example, chromophores, [1] metals, [2] catalytic units, [3] nanoparticles, [4] fluorophores [5] and even proteins [6] have been arranged at well-defined distances by means of DNA hybridization. Until recently, the main interest was focused on issues within materials science as well as on the immobilization of biomolecules.…”
mentioning
confidence: 99%
“…UV/ Vis, fluorescence, and circular dichroism (CD) spectroscopy showed that the use of G4-DNA as a template resulted in the effective communication between the ligands and the TINA molecule that was covalently attached to the 5'-end and between T and dG at the 5'-end of the dTG 4 T sequence. Only one G4-DNA possessing the TINA molecule at the 5'-end of the dTG 4 T sequence was able to yield a green-to-blue photochemical upconversion (PUC, l em = 420 nm) in the presence of [Ru(bpy) 3 ] 2 + upon excitation at 500 nm. Different DNA secondary structures can thus be used in DNA-based assemblies for PUC and the way of attachment of chromophores to DNA plays a pivotal role for the creation of a photosynthetic centre.…”
mentioning
confidence: 99%
“…15,16 Due to the accurate specificity of base-pair interactions, it is possible to obtain self-assembled DNA nanoplatforms that allow accurate positioning of various moieties with sub-nanometer precision. 17,18 The decoration of these DNA constructs with fluorophores [19][20][21][22][23] has already resulted in several studies of molecular interactions based on FRET pairs using dye-dye or dyequencher combinations.…”
Section: Photoacoustic (Pa) Tomography (Pat) Is Emerging As An In Vivmentioning
confidence: 99%